Understanding Performance Under Pressure: The Dual Role of Impostor Syndrome and Leader–Member Exchange in High-Tech Work Environments - Ryani Kusumawati, Retno; Murti, Tri Ratna; Yunanto, Kuncono Teguh (Jurnal Psikologi, 2025)
This study investigates the effects of technostress and digital self-efficacy on employee performance in digitally transformed manufacturing environments. It examines impostor syndrome as a mediating variable and leader–member exchange (LMX) as a moderating variable to understand their combined influence on work outcomes. A quantitative research design was applied, involving 236 employees from a technology-integrated manufacturing company in Indonesia. Data were analyzed using Structural Equation Modeling (SEM) in R. The results show that technostress negatively affects employee performance, while digital self-efficacy enhances it. Impostor syndrome significantly reduces performance but does not mediate the relationship between technostress or digital self-efficacy and performance across the full sample. Similarly, LMX does not significantly moderate the effect of impostor syndrome on performance. However, multigroup SEM analysis reveals that these relationships are significant among factory employees but not among office staff. These findings highlight the contextual nature of psychological responses to digital transformation and suggest that organizations should tailor interventions to different work settings. Strengthening digital self-efficacy and supportive leadership practices may help mitigate the negative effects of technostress and impostor syndrome on employee performance.